COAL MINING AND THE RESOURCE CURSE IN THE EASTERN UNITED STATES1. (1st November 2016) - Douglas, Stratford; Walker, Anne
ABSTRACT: We measure the effect of resource‐sector dependence on long‐run income growth using the natural experiment of coal mining in 409 Appalachian counties selected for homogeneity. Using a panel data set (1970–2010), we find a one standard deviation increase in resource dependence is associated with 0.5–1 percentage point long‐run and a 0.2 percentage point short‐run decline in the annual growth rate of per capita personal income. We also measure the extent to which the resource curse operates through disincentives to education, and find significant effects, but this "education channel" explains less than 15 percent of the apparent curse.